An investigation of usability problems and improvement needs on upper extremity rehabilitation equipment in Korea - Moon, Jong-Hoon; Heo, Sung-Jin; Jung, Jin-Hwa (International Journal of Advanced Science and Technology, 2019)
Background/Objectives: The purpose of this study was to investigate usability problems and improvement needs of upper extremity rehabilitation equipment (UERE) used by Korean occupational therapists.Methods/Statistical analysis: The questionnaire was administered to clinicians working as occupational therapists at 121 hospitals in Korea. A total of 182 questionnaires were analyzed, excluding 369 questionnaires with incomplete and missing responses.Findings: Of the 182 respondents, 71 (39%) therapists reported that UERE had usability problems, and 89 (48.9%) reported they needed improvement. The presence rate of nine UEREs were 36.8%– 96.7% and the usability experience was 33.5%–95.6%. UERE's usability problems and improvement needs were higher with higher clinical experience and higher in university and general hospital workers than in rehabilitation hospital workers. Usability problems for UERE had two main problems. The therapist responded that UERE was not interesting to use and that various control adjustable functions were designed to be difficult. The response to the improvement needs was reported to be level adjustable and various control adjustable.Improvements/Applications: These findings suggest that occupational therapists see problems with and require improvements in UEREs. Thesemay be the basis for future development of UERE.